Implementation of the Public Service Supervision Policy at the Office of the Ombudsman of the Republic of Indonesia Representative for South Sulawesi - Rahman, Nawir; Joenoes, Andi Fita Aisyah Chairunnisa Insani; Nur, Andi Cudai; Akib, Haedar (Universitas Negeri Makassar, 2023)
Ombudsman supervision is a representation of supervision carried out by the community or civil society groups. The way the Ombudsman works is also similar to the way civil society works, free of charge, and various other conveniences. This research aims to examine how the Public Service Oversight Policy is implemented in the Office of the Ombudsman of the Republic of Indonesia, South Sulawesi Representative. This type of research is qualitative using a descriptive approach. Data collection techniques were carried out by means of observation, interviews and documentation. The data analysis technique used consists of data collection, data display, data condensation and drawing conclusions. The research results show that researchers can categorize the implementation of public service supervision policies in the Indonesian ombudsman office representing South Sulawesi as good and have experienced improvement. As for why researchers say the implementation of public service supervision policies at the Indonesian ombudsman office representing South Sulawesi is in the good category because the communication, disposition and bureaucratic structure indicators have been running well according to the objectives and have experienced improvement.